Interactive Story for Teaching Ecosystem Topics Using Twine Application for Elementary School Students - Jalmasco, Ana Carmella; Loberes, Joyce Maan; Lasala, Nestor Jr (Journal of Basic Education Research, 2025)
Purpose of the Study. This study aims to design, develop, and evaluate EcoQuest, an interactive digital story for teaching ecosystem topics to high school students. Utilizing the Twine application, EcoQuest integrates interactive storytelling to create an engaging instructional tool for science education. Methodology. A descriptive-developmental research design, following the ADDIE model, was employed. EcoQuest was developed using Twine for interactivity, Canva for visual design, and AI-generated narration for audio. Supplementary videos were sourced from YouTube. The tool was evaluated by science education and IT experts using the DepEd Learning Resources Management and Development System (LRMDS) tool and pilot-tested with Grade 6 Elementary student for usability and engagement. Main Findings. Expert evaluations confirmed that EcoQuest met high instructional and technical quality standards, while student feedback indicated that the interactive format enhanced engagement and ease of use. The study validated EcoQuest as a viable educational tool, demonstrating its potential to support ecosystem instruction in high school science education. Novelty/Originality of this Study. This study introduces EcoQuest as a localized, interactive, and curriculum-aligned instructional material for teaching ecosystems. Unlike traditional static materials, it employs branching narratives and multimedia elements to foster student engagement. By integrating digital storytelling into science education, EcoQuest provides an innovative approach to enhancing learning experiences in environmental science.